Pemanfaatan Limbah Cangkang Telur Sebagai Pupuk Organik Pada Tanaman Terong Ungu di Desa Lengkong - Intan Bahrina (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Today, the public's knowledge of recycling waste management is still lacking. In fact, if waste recycling is carried out optimally, it can reduce waste significantly. One of the urban household waste is eggshell waste. The purpose of this activity is to increase the understanding, knowledge, and insight of the residents of Lengkong Village about the benefits of eggshells. Activities carried out in the form of site surveys, interviews before and after counseling. The material consisted of an explanation of the content and benefits of eggshells, how to make eggshell powder, and how to fertilize plants, especially purple eggplant plants. After attending counseling, the community knows the content and benefits of egg shells. After that it is used as plant fertilizer. This can reduce eggshell waste and become a more useful product.